Single Tooth Prosthetic Restoration Through Surgical CrownLengthening, Conservative Therapies and CAD-CAM Milled Restoration in Lithium-Disilicate: A Case Report - Maria Giulia Pulcini; Carlo Vitelli; Arturo Dian; Katherine Radaelli; Matteo Basso (Acta Stomatologica Croatica, 2019)
Objective. The restorative treatment of a decayed, non-vital upper premolar often requires an interdisciplinary approach. Esthetics and the entity of the masticatory loads are usually affecting the choice of procedures and materials. A conservative treatment in a case with esthetic needs and functional requirements is investigated in this case report. Materials and methods. A case of a 45- yearold woman with a severely decayed upper premolar is presented. The tooth has been previously treated in an emergency department with a provisional endodontic medication, but a further treatment has been then performed. The tooth was painful at the moment of the visit and the carious lesion appeared to invade the subgingival level. A surgical-conservative approach has been selected involving crown lengthening, endodontic treatment and a prosthetic crown with a monolithic Lithium- Silicate. Results. The rehabilitative process required 3 months, including maturation times after surgery and the placement of the provisional crown. The patient claimed to be both esthetically and functionally satisfied with the restoration. Conclusion. A conservative treatment of a severely involved tooth requires a critical evaluation of the remaining structures and a precise selection of the restorative materials. A monolithic crown could represent an ideal solution for restoring an upper premolar requiring esthetics and solid function, but the choice of a high translucent, easily polishable and possibly even chair-side prosthetic material might be an appreciable added value for clinicians.